Philosophical Encyclopedia in a Mystical Fatwā: The Sufi Readers of the "Brethren of Purity" (Iḫwān al-Ṣafāʾ) in Sixteenth-Century Cairo under Ottoman Rule - Gasimov, Kamal (Arabica, 2025)
Cairene Sufis ʿAbd al-Wahhāb al-Šaʿrānī (d. 973/1565) and his master ʿAlī l-Ḫawwāṣ (d. 939/1532) formulated an original mystical-legal theory that linked the existence of the religious obligation (taklīf) as well as the origins of Islamic law to the myth of Adam’s Fall. Expressed in the form of a fatwā, the theory synthesized numerous Islamic legal, theological, and Sufi sources, including the Epistles of the Brethren of Purity (Rasāʾil Iḫwān al-Ṣafāʾ), which is widely regarded as the first Islamic philosophical encyclopedia. This article sheds light on the remarkable parallels between the Epistles and the Sufi theory, demonstrating that al-Ḫawwāṣ and his disciple utilized the Epistlesʾ ideas to articulate their teaching on Islamic law, the human deficiency, and self-reform, and to reinforce the spiritual authority of the local Sufi šayḫs. The convergence of social crisis and eschatological expectations during the times of the Brethren in the fourth/tenth century and the Cairene Sufis in the tenth/sixteenth century brought forth the enduring relevance of the Epistle’s Adamic narratives in the late medieval period. This article delves into the Sufisʾ engagement with the Epistles within the wider scope of how the contentious works of the Brethren were received among Ottoman mystics and jurists in Cairo.